Thu gọn biểu thức
5(2x-3)(2x+3)-6(x-7)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = (x - 1)3 - x(x - 2)2 + 1
A = (x - 1)(x2 - 2x + 1) - x(x - 2)2 + 1
A = x(x2 - 2x + 1) - (x2 - 2x + 1) - x(x - 2)2 + 1
A = x3 - 2x2 + x - (x2 - 2x + 1) - x(x2 - 2x.2 + 22) + 1
A = x3 - 2x2 + x - (x2 - 2x + 1) - (x3 - 4x2 + 4x) + 1
A = x3 - 2x2 + x - x2 + 2x - 1 - x3 + 4x2 - 4x + 1
A = (x3 - x3) + (-2x2 - x2 + 4x2) + (x + 2x - 4x) + (-1 + 1)
A = x2 - x
B = (-x - 2)3 + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = (-x - 2)[(-x2) - 2.(-x).2 + 22] + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = -x[(-x)2 - 2.(-x).2 + 22] - 2[(-x)2 - 2.(-x).2 + 22] + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = -(x3 + 4x2 + 4x) - (2x2 + 4x + 8) + 2x(x2 + 2x + 4) - 4(x2 + 2x + 4) - x2(x - 6)
B = -(x3 + 4x2 - 4x) - (2x2 + 4x + 8) + 2x3 + 4x2 + 8x - (x2 + 8x + 16) - (x3 - 6x2)
B = -x3 - 4x2 + 4x - 2x2 - 4x - 8 + 2x3 + 4x2 + 8x - x2 - 8x - 16 - x3 + 6x2
B = (-x3 + 2x3 - x3) + (-4x2 - 2x2 + 4x2 - x2 + 6x2) + (-4x - 8x + 8x - 8x) + (-8 - 16)
B = -12x - 24
(6x+1)(2x-5)=12x2-30x+2x-5=12x2-28x-5
(2x+5)2-2x(2x+8)=4x2+20x+25-4x2-16x=4x+25
(3x-5)(2x-1)-(2x+3)(3x+7)+30x=6x2-3x-10x+5=6x2-13x+5
(X-1)2-(x+1)(x-1)=x2-2x+1-x2+1=-2x+2
(3x+2)(9x2-6x+4)-(3+x)(x-3)=27x3+8+9-x2=27x3-x2+17
a: Ta có: \(x^2-4x\left(3x-4\right)+7x-5\)
\(=x^2-12x^2+16x+7x-5\)
\(=-11x^2+23x-5\)
b: Ta có: \(7x\left(x^2-5\right)-3x^2y\left(xy-6y^2\right)\)
\(=7x^3-35x-3x^3y^2+18x^2y^3\)
c: Ta có: \(\left(5x+4\right)\left(2x-7\right)\)
\(=10x^2-35x+8x-28\)
\(=10x^2-27x-28\)
a: =6x-3-|x-5|
Trường hợp 1: x>=5
A=6x-3-x+5=5x+2
Trường hợp 2: x<5
A=6x-3-(5-x)=6x-3+x-5=7x-8
b: Trường hợp 1: x>=-3/2
A=2x+3+x+2=3x+5
Trường hợp 2: x<-3/2
A=-2x-3+x+2=-x-1
`a)3(2x-1)-|x-5|`
`@TH1: x-5 >= 0<=>x >= 5=>|x-5|=x-5`
`=>3(2x-1)-(x-5)=6x-3-x+5=5x+2`
`@TH2: x-5 < 0<=>x < 5=>|x-5|=5-x`
`=>3(2x-1)-(5-x)=6x-3-5+x=7x-8`
____________________________________________________
`b)|2x+3|+x+2`
`@TH1:2x+3 >= 0<=>x >= [-3]/2=>|2x+3|=2x+3`
`=>2x+3+x+2=3x+5`
`@TH2:2x+3 < 0<=>x < [-3]/2 =>|2x+3|=-2x-3`
`=>-2x-3+x+2=-x-1`
5(2x - 3)(2x + 3) - 6(x - 7)2
= 5(2x - 3)(2x + 3) - 6(x2 - 14x + 49)
= 5(4x2 - 9) - 6(x2 - 14x + 49)
= 5.4x2 + 5.(-9) + (-6).x2 + (-6).(-14x) + (-6).49
= 20x2 - 45 - 6x2 + 84x - 294
= 14x2 + 84x - 339
5(4x^2-9)-6(x^2-14x+49)=20x^2-45-6x^2+84x-294=14x^2+84x-339